The current treatment strategy for gouty arthritis - M. S. Petrova; М. M. Musiychuk; V. I. Mazurov (Современная ревматология)
Febuxostat is a non-purine selective inhibitor of isoforms of xanthine oxidoreductase (XOR), the effect of which is aimed at lowering the level of serum uric acid (UA). Febuxostat is a more potent inhibitor of XOR than allopurinol, as confirmed by that target UA levels have been achieved more frequently with febuxostat than with allopurinol, particularly in patients with high serum urate concentrations. The pharmacokinetic properties of febuxostat are not dependent on renal clearance, which distinguishes it from allopurinol and may benefit patients with chronic kidney disease. A number of studies are being conducted to further evaluate the cardiovascular safety of febuxostat and its possible positive effects in preserving renal function. Of importance is the fact that febuxostat does not require dose adjustment in elderly patients.